2022
DOI: 10.3724/abbs.2022072
|View full text |Cite
|
Sign up to set email alerts
|

A thermophilic 8-oxoguanine DNA glycosylase from <italic>Thermococcus barophilus</italic>s Ch5 is a new member of AGOG DNA glycosylase family

Abstract: 8-Oxoguanine (8oxoG) in DNA is a major oxidized base that poses a severe threat to genome stability. To counteract the mutagenic effect generated by 8oxoG in DNA, cells have evolved 8oxoG DNA glycosylase (OGG) that can excise this oxidized base from DNA. Currently, OGG enzymes have been divided into three families: OGG1, OGG2 and AGOG (archaeal 8oxoG DNA glycosylase). Due to the limited reports, our understanding on AGOG enzymes remains incomplete. Herein, we present evidence that an AGOG from the hyperthermop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…We have previously reported that OGG1 inhibits the generation of ROS, alleviates mitochondrial dysfunction, and increases the expression of IL-1β induced by particulate matter [42] . OGG1 deficiency leads to a reduction in pulmonary fibrosis development, and the mechanism is partly based on the promotion of the TGF/Smad signaling pathway by OGG1, which aggravates the development of pulmonary fibrosis [15] . Aging can lead to a reduction in lung stem cells, mitochondrial dysfunction, oxidative stress damage and telomerase shortening, and ultimately leads to the inability of lung cells to maintain homeostasis, which plays important roles in the occurrence and development of IPF, chronic obstructive pulmonary disease and other pulmonary diseases [16] .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that OGG1 inhibits the generation of ROS, alleviates mitochondrial dysfunction, and increases the expression of IL-1β induced by particulate matter [42] . OGG1 deficiency leads to a reduction in pulmonary fibrosis development, and the mechanism is partly based on the promotion of the TGF/Smad signaling pathway by OGG1, which aggravates the development of pulmonary fibrosis [15] . Aging can lead to a reduction in lung stem cells, mitochondrial dysfunction, oxidative stress damage and telomerase shortening, and ultimately leads to the inability of lung cells to maintain homeostasis, which plays important roles in the occurrence and development of IPF, chronic obstructive pulmonary disease and other pulmonary diseases [16] .…”
Section: Discussionmentioning
confidence: 99%